THE EFFECT OF SERVICE QUALITY AND COMPANY COMMITMENT ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY AT PT. KARYA SEMANGAT MANDIRI) IN MEDAN NORTH SUMATERA INDONESIA) - Lina; Sugiharto Pujangkoro; Muhammad Anggia Muchtar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Chicken production in North Sumatra increased significantly from 2020 to 2022 which indicates that the business potential of broiler raising is promising. Broiler is known as a chicken which is able to produce high quality chicken in a short time which makes it a high ranking product in poultry raising. Partnership pattern between poultry raisers and companies is the main strategy in increasing productivity and the sustainability of broiler raising business. PT. Karya Usaha Mandiri as a holding company has developed a partnership with plasma broiler raisers to advance broiler raising business. However, there is dissatisfaction of plasma broiler raisers with the service quality of PT. Karya Pahlawan Mandiri, indicated by their complaints about the lateness of DOC supply and food, and irregular technicians' visits. The objective of the research is to analyze the influence of service quality and firm commitment on plasma broiler raisers' satisfaction and loyalty and to explore the correlation between customer satisfaction and loyalty in the context of this partnership. The research uses quantitative causality method which is aimed at analyzing the cause and effect correlation between service quality and the effect of the company's involvement in customer loyalty with customer satisfaction at PT. Independent Spirit Work. The research location is at the broiler raising place, Binjai, North Sumatra. The population is 322 clients of the company, of which 140 are used as samples, taken by using simple random sampling technique. Te data are gathered by using Likert Scale questionnaire and analyzed by using Partial Least Square (PLS) technique with SmartPLS version 3. software. The results of the research show that service quality does not have any significant influence on customer loyalty but has a positive and significant influence on customer satisfaction. Customer satisfaction significantly influences customer loyalty which indicates that good service will increase satisfaction and, in turn, it will increase loyalty. Service quality does not influence customer loyalty through customer satisfaction while firm commitment influences loyalty through customer satisfaction.